Identification of suitable biomarkers for leptospiral molecular diagnosis and gene expression in Cavia porcellus linnaeus model - Kumaran, Sharmilah Kumari (2021)
Leptospirosis is one of the reemerging and neglected infectious diseases, now has become major health concerns due to their global distribution and caused a high mortality rate among humans. The severity of the disease differs based on infecting Leptospira species/serovars, age groups, and the immune status of the patients. The major challenge with leptospirosis is the nonspecific clinical manifestation, which is often confused with other febrile illnesses like dengue, malaria, influenza, meningitis, and hepatitis. The detection of Leptospira among infected patients challenging due to the following factors: a tremendous number of leptospiral strains, biphasic nature of the illness, confusion in clinical presentation, and complicated manifestations of the laboratory examinations to detect the disease. The objectives of this study were to analyze suitable molecular markers for early detection of leptospirosis and to investigate the differential gene expression during infection in the guinea pig animal model. For identifying suitable molecular diagnostic markers, genes of interest like LipL32, OmpL1, Loa22, LenA, and LigB searched against on whole-genome sequences of sixteen Leptospira strains. In this section, a bioinformatics approach of blastp search, multiple sequence alignments, pairwise score identity, phylogenetic tree construction, primary protein structure analysis, signal peptide prediction, multiple sequence alignments of B-cell epitopes prediction, and structure modeling applied to examine the suitability of the gene as a marker for diagnosis. For the in vivo study, three groups of guinea pigs tested with three different types of pathogenic Leptospira strains, and uninfected animals were kept as a control group. Blood samples were collected on the third and tenth days of post-infection from the animals. Later, the blood samples were subjected to biochemical and RNA analysis. On the thirty days of post-infection, the animals were sacrificed, and major organs of lungs, heart, kidneys, spleen, brain, and liver investigated for organ damages using the histopathological approach. The results from the bioinformatics approach shown that five conserved regions of LipL32 (LipL3212-37, LipL3264-85, LipL3287-128, LipL32137-155, and LipL32199-256), and four conserved regions of OmpL1 (OmpL1118-135, OmpL1137-151, OmpL1194-210, and OmpL1252-265) can be suitable molecular marker candidates. During the infection, the biochemical parameters like creatinine, total bilirubin, alanine transaminase, and aspartate transaminase level increased on the 10th day of post-infection, whereas hemoglobin and red blood cell inclined. For the RNA transcriptome analysis, the results revealed that beta-2-microglobulin (B2m), the gene responsible for tubulointerstitial nephritis, was highly expressed for animals infected with Leptospira interrogans on the 10th days of post-infection. The expression of B2m gene was well supported by renal histopathology as more lesions were identified in the infected animal kidneys. Thus, the studies suggested that the identified potential molecular markers and biomarker can use for the early detection of leptospirosis.